Role of Sequencing Genetic for 708 T>A of Cholesterol 7α Hydroxylase (CYPA17) in Patient with Gallstone Disease - Antesar Rheem Obead (Journal of Global Pharma Technology, 2019)
AIM: To investigated the association of the CYP7A1 gene polymorphism and analyze the sequencing of CYP7A1 gene with development of gallstone disease in Iraq population. Methods: The polymorphism were analyzed by polymerase chain reaction followed by restriction fragment length polymorphism, in two group match by age and sex: patient with gallstone (n=140) and stone-free control (n=140).Result: Novelty single nucleotide polymorphism in upstream of CYP7A1 gene was founded for PCR amplification 708 T >A in patient with gallstone and conformed by sequencing data and allelic frequencies in patient and control for T of CYP7A1 gene 38.2% vs 54.6% were significant (p=0.0001).Conclusion: The result have been demonstrated that association between the polymorphism of 708 T> A for CYP7A1 gene and an effect on cholesterol 7 α hydroxylase serum level with high prevalent of gallstone disease.Keywords: CYP7A1, Gallstone, Polymorphism, Sequencing analyzing.